Comparative Assessment of Rural Youth Entrepreneurs in Uganda and Kenya (Global Journal of Management and Business Research, 2014)
Youth entrepreneurship is a promising field for employment and poverty alleviation for young people who the majority in the developing world. While effort has been made to promote entrepreneurship among the youth in Kenya and Uganda, most of it has been targeting urban youth who compromise a small proportion of the overall youth population in the two countries. Using a mixed methods approach of semi structured questionnaires and in-depth interviews; this paper provides a comparative assessment of Rural Youth Entrepreneurs (RYE) in Uganda and Kenya. More specifically it examines the entrepreneurial environment in which Ugandan and Kenyan RYE operate and identifies their unique challenges with a view of making policy recommendations to support them. Findings reveal that there are differences among RYE in both countries in the demographic aspects of gender, level of education, marital status and household headship.
Keywords: rural youth; entrepreneurship; environment; uganda; kenya